History in Practice Interview – Prof. Susan Broomhall - Abidin, Crystal (University of Western Australia, 2012)
In early 2012, Crystal Abidin and Rukmini Pande had the opportunity to interview Susan Broomhall, Winthrop Professor of History at the Faculty of Arts at the University of Western Australia. Professor Broomhall is a historian of early modern Europe who specialises in the history of women and gender, as well as the role of scholarly histories in heritage tourism and arts industries. She is also one of the Chief Investigators at the Australian Research Council Centre of Excellence for the History of Emotions.